PENGUATAN JIWA NASIONALISME DAN PATRIOTISME BAGI GENERASI MUDA KABUPATEN FLORES TIMUR MELALUI PASKIBRAKA - Pilipus Wai Lawet (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The rapid development of globalization and the increasing influence of foreign cultures have the potential to weaken the sense of nationalism and patriotism among the younger generation. Therefore, strategic efforts are needed to instill and strengthen national values through educational and character-building activities. This community service program aims to strengthen the spirit of nationalism and patriotism among youth through the selection and training process of prospective Paskibraka members in East Flores Regency. The method used is a participatory approach implemented through several stages, including socialization and recruitment, administrative selection, health and parade tests, marching drills (PBB) and physical fitness tests, national insight assessment, and personality evaluation. The results show that all 59 participants who took part in the selection process not only underwent a recruitment mechanism but also experienced character development. Participants demonstrated improvements in discipline, teamwork, leadership, and understanding of national values. Thus, the Paskibraka selection program in East Flores Regency contributes significantly to strengthening the nationalism and patriotism of the younger generation as future leaders of the nation.